2021
DOI: 10.1371/journal.pone.0247264
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus infection among treatment-naive HIV-1 infected patients in Ethiopia

Abstract: Subclinical human cytomegalovirus (HCMV) replication is associated with immune dysfunction in immuno-suppressed antiretroviral therapy (ART) naive HIV infected individuals. No data is documented in Ethiopia so far concerning HCMV co-infection among HIV infected individuals. Hence, this study was aimed at generating data regarding the prevalence of active HCMV infection among treatment-naive HIV-infected individuals from Ethiopia. For this purpose, we enrolled 97 treatment-naive HIV infected study subjects in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…The Seroepidemiology variation in the prevalence of HCMV infection may rely on convenience samples from patients at a particular health institution, Regarding the HCMV PCR in the current study, only 3.33% (3/90) of the study subjects were PCR positive for HCMV-DNA. This is consistent with the other reports from Ethiopia which were detected at 4.1% [11] and South Africa, which were reported to be 5.2% [15]. In addition, our findings were relatively lower than findings from Tanzania (22.6%) and Kenya (17%) [16].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The Seroepidemiology variation in the prevalence of HCMV infection may rely on convenience samples from patients at a particular health institution, Regarding the HCMV PCR in the current study, only 3.33% (3/90) of the study subjects were PCR positive for HCMV-DNA. This is consistent with the other reports from Ethiopia which were detected at 4.1% [11] and South Africa, which were reported to be 5.2% [15]. In addition, our findings were relatively lower than findings from Tanzania (22.6%) and Kenya (17%) [16].…”
Section: Resultssupporting
confidence: 91%
“…Several epidemiological studies on seroprevalence of HCMV infection in HIV-positive individuals has been published. In line with other reports from Ethiopia, Nigeria, and Sudan, the HCMV IgM seroprevalence in those studies was 12.4%, 11.7%, and 7.1% respectively [11] [12] [13]. However, the magnitude of the HCMV in our study is lower than those reported from these African countries.…”
Section: Resultssupporting
confidence: 89%
“…Serious clinical conditions such as retinitis, pneumonia encephalitis, and enteritis may occur as an effect of the virus in individuals who do not receive ART. If the diagnosis of CMV is delayed in individuals with HIV, the deficiency in the immune system with the development of viremia accelerates the progression of HIV disease and causes an increase in mortality [25]. In the study of Gronborg et al involving HIV patients, the prevalence of CMV pneumonia ranged from 20% to 60% in patients with pulmonary symptoms, while the cause of enteritis was found in 0-14% of CMV in patients with gastrointestinal symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Seroprevalence of CMV infection in people living with HIV (PLWH) is also high, ranging from 50% to above 90% [3,4]. Detectable CMV viral loads are associated with increased mortality, even in the era of highly active antiretroviral therapy (HAART) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…These infections last their entire life and can antagonize the immune system. The effect is more important among PLWH who are not on ART than those on ART [5].…”
Section: Introductionmentioning
confidence: 99%